LIFE GIVEN FOR THE SCIENCE (ABOUT EKATERINA VLADIMIROVNA ELLADY) - S. N. Kutuzova (Труды по прикладной ботанике, генетике и селекции)
The article describes the way of life of N. I. Vavilov’s colleague Ekaterina Vladimirovna Ellady and her contribution to botanical systematics, geographical and phylogenetic study of worldwide diversity of cultivated and wild flax held in the collection of VIR.